PENINGKATAN KREATIVITAS GURU MELALUI PENGEMBANGAN KEPEMIMPINAN MELAYANI DAN EFIKASI DIRI GURU PNS - Dwi Ari Lita Nugroho Ningtyas; Sutji Harjanto; Sumardi Sumardi (JURNAL MANAJEMEN PENDIDIKAN, 2022)
IMPROVING TEACHER CREATIVITY THROUGH THE DEVELOPMENT OF SERVANT LEADERSHIP AND SELF EFFICACYThis  research  implemented  a  correlational  research  and  SITOREM  analysis  which was consist of two independent variables, they were Serving Leadership and Self-.Efficacy and one variable thatwass tied to Teacher Creativity. This research was conducted at MA Negeri in Bogor Regency in 2021. The research population  consist of 147 teachers and there were 108 samples which selected using proportional random sampling. The method used in this research was by conducting survey and data analysis techniques followed by statistical testing and simple linier regression as well as multiple linier regression. The research result were as follow: firstly, there was a significant positive relationship between the  serving leadership (X1) and teacher creativity (Y) variable in the form of the regression equation Ŷ= 65,167 + 0,504 X1 and the correlation coefficient  ry1 = 0,511 and the coefficient of determination r2y1 = 0,261. Second, there is a significant positive relationship between sel efficacy (X2) and teacher creativity with regression of the equation form Ŷ= 62,883 + 0,482 X2 and the path coefficient ry2 = 0,584 and the coefficient of determination r2y2 = 0,342. Third, there is a positive and significant relationship between the serving leadership variable (X1) and self efficacy (X2) together with teacher creativity (Y) expressed in the form of regression equation Ŷ= 39,904 + 0,305 X1 + 0,366 X2 with the subordinate coefficient ry12 = 0,646 and the coefficient of determination r2y12 = 0,417. Based on these things, it could be argued that teacher creativity could be increased throught increased serving leadership and self efficacy.